'FROG, WHERE ARE YOU?': A STUDY ON BAHASA INDONESIA INTERFERENCE IN JAVANESE CHILDREN'S SPEECH - Dian Wahyunianto (Leksema: Jurnal Bahasa dan Sastra, 2021)
The coexistence of Bahasa Indonesia and Javanese has become an issue in the Javanese language preservation. Such strong contact is finally resulting in bilingual individuals in which language interference often occur. In this study, however, is aiming at describing how and why Bahasa Indonesia is interfering Javanese in Javanese children speech. By using task-based approach by Grosjean, this study manipulated language production in Javanese children using wordless narrative book Frog, Where Are You? created by Mercer Mayer. The results show that Bahasa Indonesia is interfering Javanese in phonic, morphological, syntactic, lexical, and even semantic aspects. Nevertheless, lexical level interference is the most noticeable interference since both language share quite similar structure. It is believed that, in sociolinguistics perspective, Bahasa Indonesia has gradually shift Javanese gradually. It is also seen that Javanese children with strong exposure of Bahasa Indonesia are eventually perceive more Bahasa Indonesia structure than Javanese.